First report of the use of long‐tapered sirolimus‐eluting coronary stent for the treatment of chronic total occlusions with the hybrid algorithm. Issue 5 (7th February 2018) - Zivelonghi, Carlo; van Kuijk, Jan P.; Nijenhuis, Vincent; Poletti, Enrico; Suttorp, Maarten J.; van der Heyden, Jan A. S.; Eefting, Frank D.; Rensing, Benno J.; ten Berg, Jurrien M.; Azzalini, Lorenzo; van den Brink, Floris S.; Ribichini, Flavio; et al.
Abstract: Background: Coronary chronic total occlusions (CTO) usually coexist with diffusely diseased coronary segments proximal and/or distal to the CTO segment. During percutaneous treatment of CTO, multiple overlapping stents are often needed to treat these long lesions. Objectives: Aim of this study is to report the first use of long, tapered coronary sirolimus‐eluting stents (SES) in this setting. Methods and results: This is a retrospective analysis of 100 consecutive patients undergoing CTO recanalization following the hybrid algorithm. Procedural success rate was 89% (11 failures). Among the successful cases, "conventional" drug‐eluting stents(DES) were used in 40(44.9%) patients, while in 49(55%) patients long‐tapered SES were attempted with a success rate of 98% (1 cross‐over to regular stents). Total stent length in the long‐tapered DES group was higher compared to the "conventional" stenting group (76 ± 28 mm vs 46 ± 22 mm, P < .001), with a similar total number of stent (1.6 ± 0.8 vs 1.9 ± 0.8). At quantitative coronary analysis, proximal and distal segment involvement was more extended in patients undergoing long‐tapered stenting, with longer overall lesion length. No differences in periprocedural complications and clinical outcomes at a mean follow‐up of 303 ± 179 days were observed. Conclusions: The use of long tapered coronary DES is technically feasible and safe for the percutaneous treatment of CTOs, especially for patients presenting with long lesions.